Pregnancy management of women with kidney transplantation - Kovács, Dávid ágoston (Interv Med Appl Sci, 2015)
Women with renal disease, besides many dysfunctions, face increasing infertility and high-risk pregnancy due to uremia and changes of the hormonal functions. After renal transplantation, sexual dysfunction improves, providing the possibility of successful pregnancy for women of childbearing age. However, kidney transplanted patients are high-risk pregnant patients with increased maternal and fetal risks, and the graft also may be compromised during pregnancy; most studies report on several successive deliveries due to multidisciplinary team management. In clinical practice, the graft is rarely affected during the period of gestation. Fetal development disorders are also rare although preterm delivery and intrauterine growth retardation are common. For now, several studies and clinical investigations proved that, under multidisciplinary control, kidney transplanted female patients are also possible to have safe pregnancy and successful delivery. There are conflicting data in the literature about the prevention of complications and the timing of pregnancy. Herein, we would like to present some experience of our centre. A total of 847 kidney transplantations have been performed between June 1993 and December 2013 with 163 childbearing aged females (18–45 years) in our center. We report on three kidney transplanted patients who have given birth to healthy newborns. In our practice, severe complications have not been observed.